Ebla and its archives: texts, history, and society - Archi, Alfonso (Studies in ancient Near Eastern records, 2015)
Part I. History, language, and texts -- Part II. Society and economy -- Part III. Political relations -- Part IV. Religion -- Part V. Silver and gold